2018
DOI: 10.1007/s11548-018-1727-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and correlation analysis of computed methods to convert conventional 2D radiological hindfoot measurements to a 3D setting using weightbearing CT

Abstract: This study shows a good and reliable correlation between the [Formula: see text] and [Formula: see text]. However, the [Formula: see text] overcomes the shortcomings of inaccuracy and provides valuable spatial data that could be incorporated during computer-assisted surgery to assess the multiplanar correction of a hindfoot deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 50 publications
0
43
0
1
Order By: Relevance
“…9,17 Computer Aided Design (CAD) operations in 3-matic v12 (Materialise, Haasrode, Belgium) computed the anatomical landmarks and axes. 8,46 The apex malleolus lateralis, anterior tubercle, and posterior tubercle were respectively computed as the most distal, anterior, and posterior point of the distal fibula ( Figure 4A). The fibular shaft axis was computed as the fibular best-fit longitudinal axis.…”
Section: Specimensmentioning
confidence: 99%
“…9,17 Computer Aided Design (CAD) operations in 3-matic v12 (Materialise, Haasrode, Belgium) computed the anatomical landmarks and axes. 8,46 The apex malleolus lateralis, anterior tubercle, and posterior tubercle were respectively computed as the most distal, anterior, and posterior point of the distal fibula ( Figure 4A). The fibular shaft axis was computed as the fibular best-fit longitudinal axis.…”
Section: Specimensmentioning
confidence: 99%
“…4,7,10,15,16 Recent studies have shown how the different angles used to assess HA may differ substantially between radiographs, traditional CT, and WBCT, suggesting that 3D weightbearing measurements represent a major step forward to detect the “true alignment.” 9,13,22 In addition, this technology can provide a digitally reconstructed radiograph, similar to traditional radiography with the advantage of no rotation bias. 4,8 Common measurements, such as the long axial view (termed HACT), can be taken using this reconstruction to evaluate HA.…”
Section: Introductionmentioning
confidence: 99%
“…9,13,22 In addition, this technology can provide a digitally reconstructed radiograph, similar to traditional radiography with the advantage of no rotation bias. 4,8 Common measurements, such as the long axial view (termed HACT), can be taken using this reconstruction to evaluate HA.…”
Section: Introductionmentioning
confidence: 99%
“…(An alternative approach, not considered here, could involve redefinition of anatomical measurements using features more readily tractable by image analysis than morphological landmarks. 15 )…”
Section: Introductionmentioning
confidence: 99%
“…The proposed algorithm is applied to data of 24 subject volunteers acquired with a specialized extremity CBCT scanner. 23 Extremity CBCT systems provide the unique capability for weight-bearing three-dimensional (3-D) imaging of the knee 4,15,24 and foot. 15,24,25 Development of diagnostic applications of this new modality will benefit from improvements in the workflow, repeatability, and reliability of anatomical measurements that are anticipated with the automatic algorithm.…”
Section: Introductionmentioning
confidence: 99%